Formulation, Development, and In Vitro Evaluation of a CD22 Targeted Liposomal System Containing a Non-Cardiotoxic Anthracycline for B Cell Malignancies - Nivesh K. Mittal; Bivash Mandal; Pavan Balabathula; Saini Setua; Dileep R. Janagam; Leonard Lothstein; Laura A. Thoma; George C. Wood (MDPI AG, 2018)
Doxorubicin cardiotoxicity has led to the development of superior chemotherapeutic agents such as AD 198. However, depletion of healthy neutrophils and thrombocytes from AD 198 therapy must be limited. This can be done by the development of a targeted drug delivery system that delivers AD 198 to the malignant cells. The current research highlights the development and in vitro analysis of targeted liposomes containing AD 198. The best lipids were identified and optimized for physicochemical effects on the liposomal system. Physiochemical characteristics such as size, ζ-potential, and dissolution were also studied. Active targeting to CD22 positive cells was achieved by conjugating anti-CD22 Fab' to the liposomal surface. Size and ζ-potential of the liposomes was between 115 and 145 nm, and −8 to−15 mV. 30% drug was released over 72 h. Higher cytotoxicity was observed in CD22+ve Daudi cells compared to CD22−ve Jurkat cells. The route of uptake was a clathrin- and caveolin-independent pathway. Intracellular localization of the liposomes was in the endolysosomes. Upon drug release, apoptotic pathways were activated partly by the regulation of apoptotic and oncoproteins such as caspase-3 and c-myc. It was observed that the CD22 targeted drug delivery system was more potent and specific compared to other untargeted formulations.